Effects of metallic objects on specific absorption rate in the human head for 915 and 1900 MHz mobile phones - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2006)
This paper presents the numerical evaluation of the specific absorption rate (SAR) inside the human head induced by cellular phones at frequencies 915MHz and 1900MHz by including a metallic spectacle frame and metallic tooth caps. Calculations of the absorption are performed by distinguishing the electrical properties of up to 13 tissue types based on anatomically real head and hand models derived from specially for this work recorded MRI scans of 2mm thickness. The numerical calculations are performed using the Finite Difference Time Domain (FDTD) algorithm with mesh sizes of 2mm. The calculated local SAR values are averaged over 1g and 10g tissues as proposed by IEEE standards. It is shown that, the existence of a metallic spectacle frame may cause an increase in SAR values. However, the results demonstrate that, metallic tooth caps have negligible influence on the SAR values. The interpretation of the computational results in terms of international safety guidelines for human health indicates that the specific absorption rate stays within the limits proposed by CENELEC and IEEE standards for the maximum allowed transmitter power levels in the GSM-, DECT- and PCS-systems.
Keywords: electromagnetic radiation; specific absorption rate; mobile phones; safety standards; method of finite differences; ELECTROMAGNETIC ABSORPTION; SAR; SPECTACLES; 900-MHZ; MODELS